Canada before television : radio, taste, and the struggle for cultural democracy (McGill-Queen's University Press, 2016)
"The work is a history of the first phase of broadcasting in Canada, roughly comprising the years 1920-1956, during which radio was still the dominant technology for reaching local and national audiences. Its focus is English-speaking Canada's radio industry, which developed differently from the Francophone side and was subject to direct competition from American broadcasting outlets. The work argues that broadcasters in Canada before television spent considerable money, time, and effort attempting to figure out which kinds of programs people liked and how listeners could be engaged by radio. Assumptions about listeners' habits and dispositions varied, and within a mixed private-public broadcasting industry there was no shortage of free advice about what should go on the air or how to make programs. Though maligned as elitists by some of their contemporaries, public broadcasters (working through the CBC from 1936 on) hoped to realize a democratic vision of broadcasting, a vision in which programs appealing to mainstream tastes remained prominent, but with no listeners 'left behind'. In six topical chapters (intimacy, America, Britain, regulation, music, minority) the work mines archival sources from Canada, the US, and the UK, as well as the existing historiography of broadcasting. It is not in-depth analysis of programming content, but rather concerns itself with the ways that Canadian broadcasting's evolving structure, the goals of broadcasters, prevailing and shifting tastes and norms, and listeners' expectations all affected programs and policies."--